Internasionaalregtelike Perspektiewe op die Switserse Neutraliteitspraktyk en Ondersteuning van die Boererepublieke tydens die Anglo-Boereoorlog, 1899 - 1902: Deel 1: Historiese Grondslae van die Switserse Neutraliteitspraktyk - Raath, A. W. G.; de Freitas, S. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
The Swiss practice of neutrality is the outcome of a process which has taken centuries to develop. One of its characteristics is that it developed out of common law and is partly based on common law even today. At the beginning of the 18th century it was still quite consistent with neutrality for a neutral country to permit troops of belligerent countries to march through its territory. A neutral country could even provide the belligerent parties with soldiers and war material. At the end of the 18th century beginnings of a modern concept of neutrality developed, which provided that the national territory of a neutral country must be left out of the acts of war, that belligerent parties must not be assisted with material help and that all belligerent parties should receive identical treatment. However, these new principles were slow to gain acceptance. Far into the 19th century they were still disregarded and violated. In the second half of the 19th century, the Swiss interpretation of neutrality was largely informed by the dominant ideology of positivism of the time. This positivistic position provided the Swiss government with a convenient motivation for not approaching Brittain to end the Anglo-Boer War of 1899 to 1902. However, the upcoming concerns about the humanitarian position of the women and children in the concentration camps engendered strong feelings in favor of intervention among the Swiss population. Although the Swiss government managed to maintain its policy of non-intervention, the outcry against theimmoral treatment of the Boer women and children brought the Swiss government to the verge of a major constitutional crisis. The outcome of this was the emergence of new concerns about justice and the humanitarian treatment of civilians in times of war.